Isolation and Identification of Flavonoid Constituents from of Achillea conferta DC. - S Saeidnia; N Yassa; AR Gohari; A Shafiee (Institue of Medicinal Plants, ACECR, 2005)
Background: Achillea (Asteraceae) comprises 115 species, which are mainly distributed in Europe, Asia and North Africa and also is an introduced plant in the New World. Nineteen species of the genus were described in the Flora Iranica, of which Achillea conferta DC. is found in the central and western regions of Iran as well as Iraq. However, a survey of the literature revealed that only a few works deal with the composition of flavonoid constituents of A. conferta and there is no report on the Iranian one. Objective: Here we aim to describe the isolation and identification of flavonoid aglycons in Achillea conferta collected from Talegan mountain in Iran in order to compare with the flavonoid constituents of other samples of A. conferta. Method: The top flowers of Achillea conferta DC. (Compositae) were collected from Taleghan area in spring 2000. The powdered plant was extracted by percolation method with methanol. This crud extract was washed with petroleum ether and chloroform. The resulted extract was concentrated in vacuum distillator and then subjected to paper chromatography (whatman NO: 1), using acetic acid 2%, 15% and BAW as solvents. The spots were detected under UV lamp at 366 nm. Results: Three main flavonoid aglycons were identified as luteolin, chrysoeriol and quercetin by using UV spectra (shift reagents), H- NMR data and Mass spectra in comparison with those reported in references. Conclusion: In this species, highly methoxylated flavonoids could not be observed. Chrysoeriol is the only methoxylated flavon separated from methanol extract of Iranian Achillea conferta.